(untitled) (Global Journal of Science Frontier Research, 2017)
In 140 specimens of five carangid species were captured in Playa Las Barrancas and El Cabezo Reef, Veracruz Reef System National Park, Veracruz State, Southern Gulf of Mexico:Caranx crysos (n=51), Caranx hippos (n=18), Chloroscombrus chrysurus (n=28), Oligoplites saurus (n=24) and Trachinotus carolinus (n=19), a total of 44 helminth species were recovered, distributed as follows: 18 digeneans (17 adults, and 1 metacercaria), 12 monogeneans, 9 nematodes (6 adults, and 3 larvae), 4 cestodes (all larvae), and 1 acanthocephalan (juvenile). Parasite of helminths species with the highest prevalence in five communities were Pseudobicotylophora atlantica and Amphipolycotyle chloroscombrus, while species with mean intensity were Hurleytrema catarinensis; and the nematode Hysterothylacium sp., was registered in all five communities.